Participation in extracurricular activities by students attending assisted and prestige schools in Trinidad - Worrell, Frank C.; Bucknavage, Leah B. (School of Education, UWI, St. Augustine, 2004)
Participation in 19 extra-curricular activities was investigated in 1,312 secondary school students attending assisted and/or prestige schools in Trinidad. The sample was 60 percent male, 21 percent African descent, 41 percent East Indian descent, and 30 percent Mixed descent. Research questions focused on mean number of activities and participation rates in activities by ethnicity and gender, and the relationship between extra-curricular participation and student achievement and attitudes. Results indicated that ethnic and gender groups participated in the same number of activities on average, although there were gender-stereotypical rates of participation in some activities. Participation in steelband, solo instruments, debating, and chess were associated with higher student achievement, as was length of time on student council. Females reported playing in steelbands at significantly higher rates than males, and students of East Indian descent reported higher rates of involvement in cricket and lower rates in steelband than their peers of the same gender
Keywords: Assisted schools; Denominational schools; Secondary school students; Extracurricular activities; Student participation; Trinidad and Tobago